The Inconsistency a Village Planning and Budgeting (A Study Muna Regency, Southeast Sulawesi Province) - Jopang Jopang; Faturachman Alputra Sudirman (Iapa Proceedings Conference, 2021)
The consistency between the planning and budgeting processes is a form of implementing good governance in the village. This study aims to analyze the inconsistency of village planning and budgeting in Muna Regency. This study uses a qualitative approach with natural settings and in-depth investigation. This method is carried out by studying village planning and budgeting documents, starting from the process to the output. The study sites were conducted in 15 villages in Muna Regency, which were divided into two regions / locations. Region one consists of 7 villages, which are located on the waterfront. Furthermore, the second area consists of 8 villages located in the mainland area (not by the sea). Secondary data retrieval is limited based on the time period of the budgeting namely the period of the 2016 and 2017 fiscal years. Data collection procedures through document study and focus group discussions. Focus group discussions involve village officials, members of the Village Consultative Body, and the Village Community Empowerment Institute. The results found: first, the implementation of the village planning and budgeting process in Muna District was not entirely consistent. Inconsistency is shown by the activities contained in the Village Budget/Anggaran Pendapatan Belanja Desa (APBDes), but not stated in the Village Government Work Plan/Rencana Kerja Pemerintah Desa (RKPDes) that has been previously determined. Second, village planning and budgeting do not yet have a reciprocal relationship, that is, a plan requires a budget while the budget is nothing but the financial instrument of the plan. Third, the inconsistency between the RKPDes and the ABPDes is intentional, where the motive is the desire to be able to distribute until the ceiling / budget allocation has been determined by giving a greater portion to the interests of the village government.